Finding values in lignin: A promising yet under-utilized component of the lignocellulosic biomass - Jassal, Vidhisha; Dou, Chang; Sun, Ning; Singh, Seema; Simmons, Blake A.; Choudhary, Hemant (Frontiers in Chemical Engineering, 2022)
This article outlines the technical and economic potentials of lignin in unlocking sustainable biorefineries. The benefits of using this highly functionalized biopolymer for the growth of sustainable economy have been highlighted. But practically, the possibility of commercially substituting petroleum oil with lignin is still not very high as the estimated biofuel production cost is 2-3 times higher than the former one. However, with the advancement in technology and more efficient measures by biorefineries such as storing and processing the biomass near the field so as to reduce the transportation cost, it is possible to gain higher profits. Companies like Domtar, Stora Enso, Borregaard’s LignoTech, VITO, and Chemelot InSciTe are working really hard in order to promote commercial value of lignin. The growth of lignin market after the start-up production at various sites has been discussed in this review. Combining the complete ‘start-to-finish’ analysis with economic evaluation gives a pragmatic overview of the possibilities whether lignin will join petroleum oil as an efficient and cost-effective renewable source.